(3QSGFd UZjQI aj GdcjejGA CZdHgG ZjQ eYfhf ; hChdgG WQjb GdLGeYs - (3eLghds
(3ChdgG (B:s
(3HSe Gddg GYde Cf GdMceGA deG XaQhG HGdeGOI hYQahG efgG GdCHhGH GdeTghQI YfOge adGM dge HYO Pdc WQjb gj CTQagG JSei YfOge HGdWQjb GdLGeY dCfgG LeYJ GdWHGFY s
(3BNQgG (B:s
(3UaI QLQGL jfHZj Cf Jchf GdedGZe efg aGfg UMjM eMce aGYQa bOQgG jDNP QWdj edM bdj WhQj LjO hQWd LjQ MGQ jSMbGf fGYeG hjYed efg eGQGS HGdNd GdMGQb Jes
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdcjejGA hGdWHjYjGJs